A compact four states radiation-pattern reconfigurable monopole antenna for Sub-6 GHz IoT applications - Boukarkar, Abdelheq; Rachdi, Satouh; Mohamed Amine, Mrabet; Sami, Baguigui; Benziane Khalil, Adda (International journal of electronics and communications, 2023)
A simple design of a compact radiation-pattern reconfigurable monopole antenna with different states is proposed. The antenna switches between four radiation patterns by introducing two parasitic elements, which can be controlled by activating or deactivating two p-i-n diodes. The antenna presents two opposite-direction unidirectional modes, one bidirectional mode, and one omnidirectional mode. Few lumped components are used in the DC bias network, reducing the fabrication cost and antenna complexity. An antenna prototype is fabricated and tested to validate the proposed approach. The common operating frequency band measured realized gain and realized efficiency ranging from 3.36 GHz to 3.6 GHz, 2.13 dBi to 4.93 dBi, and 62% to 82%, respectively. The antenna presents the benefits of a low profile, simple DC bias, and the ability to suppress radiations in unwanted directions. Therefore, the antenna can be easily integrated and used in different wireless systems requiring pattern diversity, for instance, in Sub-6 GHz Internet of Things (IoT) Applications.